2014
DOI: 10.1038/ncomms4833
|View full text |Cite
|
Sign up to set email alerts
|

The tobacco genome sequence and its comparison with those of tomato and potato

Abstract: The allotetraploid plant Nicotiana tabacum (common tobacco) is a major crop species and a model organism, for which only very fragmented genomic sequences are currently available. Here we report high-quality draft genomes for three main tobacco varieties. These genomes show both the low divergence of tobacco from its ancestors and microsynteny with other Solanaceae species. We identify over 90,000 gene models and determine the ancestral origin of tobacco mosaic virus and potyvirus disease resistance in tobacco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
412
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 510 publications
(428 citation statements)
references
References 60 publications
(90 reference statements)
10
412
0
6
Order By: Relevance
“…Texas Marker-1 (TM-1), which is widely used as a genetic standard 1,10 . We generated a genome sequence containing two-to about fourfold longer sequence scaffolds (N50 = 1,600 kb) than that produced for other allopolyploid species Brassica napus (N50 = 764 kb) 9 , Nicotiana tabacum sequencing of allotetraploid cotton (Gossypium hirsutum l. acc.…”
mentioning
confidence: 99%
“…Texas Marker-1 (TM-1), which is widely used as a genetic standard 1,10 . We generated a genome sequence containing two-to about fourfold longer sequence scaffolds (N50 = 1,600 kb) than that produced for other allopolyploid species Brassica napus (N50 = 764 kb) 9 , Nicotiana tabacum sequencing of allotetraploid cotton (Gossypium hirsutum l. acc.…”
mentioning
confidence: 99%
“…To obtain insight into the metabolic regulation of amino acids during protoxylem vessel element differentiation, we conducted RNA-seq analysis of VND7-VP16-GR BY-2 cells treated with DEX or mock for 0, 6, 12, 24, and 36 h. After the de novo assembly of sequence reads based on the tobacco reference genome (Sierro et al, 2014), we obtained 74,932 unique contigs from the mRNA-seq data for the VND7-VP16-GR BY-2 cells. Previous work reported the set of direct targets of Arabidopsis (Arabidopsis thaliana) VND6 and VND7 (Ohashi-Ito et al, 2010;Zhong et al, 2010;Yamaguchi et al, 2011); based on this, we first examined the expression patterns of genes homologous to the 63 VND7 direct target genes reported by Yamaguchi et al (2011).…”
Section: Transcriptome Analysis Of Vnd7-vp16-gr By-2 Cellsmentioning
confidence: 99%
“…Tobacco genome revealed its ancestral origin, familial and taxonomical relation with tomato and potato and different biochemical pathways involved in alkaloid biosynthesis. In addition, the study confirmed that disease resistance to different viruses in tobacco is caused by genomic deletion of the S-form eIF4E1 locus (Sierro et al, 2014). The findings are useful to screen the resistant genotypes to virus-caused diseases not only in tobacco but also in other plants while these data are used as the reference.…”
Section: * Ingeniero Agrónomomentioning
confidence: 55%